Is Discrimination of 13C in potato leaflets and tubers an appropriate trait to describe genotype responses to restrictive and well-watered conditions? - Ramírez, D.; Rolando, J.L.; Yactayo, W.; Monneveux, P.; Quiróz, R. (Wiley, 2015)
The article objectives were: (i) to compare physiological performance and biomass accumulation among genotypes along the growing period and (ii) to test the reliability of Δleaflet and Δtuber to determine key mechanisms responsible of the varietal differences in biomass accumulation and tuber yield under different water availability levels.